(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Artificial intelligence is one of the most advanced fields in the modern era, and it has proven its efficiency in many fields such as medicine, education, business, industry, transportation, and others. Artificial intelligence aims to understand the nature of human intelligence, by creating computer programs capable of simulating human behavior characterized by intelligence, so that the computer can make independent decisions without referring to its user. There is no doubt that granting artificial intelligence a legal personality means granting it an independent legal status, enjoying rights, such as the right to an independent financial entity, the right to a name, as well as intellectual property rights, and also bearing obligations and responsibilities, such as the obligation to compensate for damages resulting from its illegal actions, and this is the subject of our research that focuses on the nature of the legal personality of artificial intelligence.